Economic crisis in mass representations of Russians - Semenov, A.V. (Perm Federal Research Centre Journal, 2021)
During the post-Soviet period, Russians have experienced several economic crises, which have become a prism for assessing the political situation in the country and the direction of its development. In this article, based on mass polls data by the Public Opinion Foundation (FOM) and Russian Public Opinion Research Center (VCIOM) in 2019-2020, the author has reconstructed public perceptions of the economic crisis, identified the groups more inclined to admit the crisis in the country, described adaptive mechanisms they used, and assessed if the feeling of crisis affect the public trust in political institutions. A quantitative textual analysis of the open entry responses concerning the characteristics of the economic crisis shows that it is consistently associated with the gap between available and desired levels of consumption and economic security, rather than a sharp decline in macroeconomic indicators. Rising prices, low living standards and low wages are the most frequent indicators of the crisis in the responses. Respondents in the low-income categories and younger cohorts are the most susceptible to the crisis. Adaptation mechanisms had already begun to form on the eve of the main wave of the pandemic in March 2020, but the increased level of uncertainty about the future determined the demand for trustful information on the state of affairs in the economy. The study also shows that the feeling of crisis is associated with the decreased distrust of governmental bodies. In general, the work demonstrates the importance of studying subjective assessments of well-being and their role in structuring information about processes in politics and economy.